2017 IEEE 5th International Conference on Future Internet of Things and Cloud (FiCloud) 2017
DOI: 10.1109/ficloud.2017.30
|View full text |Cite
|
Sign up to set email alerts
|

A Holistic Monitoring Service for Fog/Edge Infrastructures: A Foresight Study

Abstract: Although academic and industry experts are now advocating for going from large-centralized Cloud Computing infrastructures to smaller ones massively distributed at the edge of the network, management systems to operate and use such infrastructures are still missing. In this paper, we focus on the monitoring service which is a key element to any management system in charge of operating a distributed infrastructure. Several solutions have been proposed in the past for cluster, grid and cloud systems. However, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 23 publications
1
34
0
Order By: Relevance
“…5.0.6 Fog Resource Monitoring. Few studies in the literature propose monitoring schemes for fog resources [151]. Monitoring is useful when multiple operators use a fog node, or when a fog node is located in a location where many users use the fog node.…”
Section: Mobile Fogmentioning
confidence: 99%
“…5.0.6 Fog Resource Monitoring. Few studies in the literature propose monitoring schemes for fog resources [151]. Monitoring is useful when multiple operators use a fog node, or when a fog node is located in a location where many users use the fog node.…”
Section: Mobile Fogmentioning
confidence: 99%
“…Naha et al [14] suggested that the resource monitoring should able to detect the future needs of the applications to avoid the SLA violation. Liyanage et al [15] has given a foresight study on Fog/Edge infrastructures with requirements and specifications of Fog/Edge monitoring service. The study presented a classification of monitoring architectures, services, and tools of existing Cloud and distributed systems and suggested that our community should propose effective monitoring service in Fog/Edge computing.…”
Section: Related Workmentioning
confidence: 99%
“…. ) that we identified in our previous study [10]. They may be expressed as chains of elementary algebraic functions such as aggregate, filter, join, split .…”
Section: The Mutualized Placement Problemmentioning
confidence: 99%
“…We proceed using elementary functions deduced from our previous work [10] to express the monitoring processing requests in a unified way. The best composition of functions is then achieved by mutualizing as many functions as possible among the different tenants while taking into account their QoS constraints and the infrastructure capabilities.…”
Section: Introductionmentioning
confidence: 99%